2012
DOI: 10.2752/175303712x13479798785814
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Influences on Individual Differences in Frequency of Play with Pets among Middle-Aged Men: A Behavioral Genetic Analysis

Abstract: There is growing evidence that pet ownership and human–animal interaction (HAI) have benefits for human physical and psychological well-being. However, there may be pre-existing characteristics related to patterns of pet ownership and interactions with pets that could potentially bias results of research on HAI. The present study uses a behavioral genetic design to estimate the degree to which genetic and environmental factors contribute to individual differences in frequency of play with pets among adult men.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
(132 reference statements)
1
4
0
Order By: Relevance
“…Our findings are in line with a previous study in 614 male twin pairs (mean age 55.4) from the US Vietnam Era Twin Study of Aging 34 . In that study, the response to the question “During the past 30 days, how often did you play with pets” was estimated to have heritability of 37% (95% CI, 28–44%) and <10% due to shared environmental factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in line with a previous study in 614 male twin pairs (mean age 55.4) from the US Vietnam Era Twin Study of Aging 34 . In that study, the response to the question “During the past 30 days, how often did you play with pets” was estimated to have heritability of 37% (95% CI, 28–44%) and <10% due to shared environmental factors.…”
Section: Discussionsupporting
confidence: 93%
“…These estimations rely on the underlying assumptions that MZ and DZ twin pairs share environment to a similar degree, that MZ twins share their entire genome, and that DZ twins on average share 50% of their segregating alleles 33 . A previous study of twin pairs aged 51–60 indicated that genetic factors account for up to 37% of the variation in the frequency of pet play and that less than 10% is attributable to the shared childhood environment 34 indicating a strong contribution of genetic factors to the amount of playful interaction with pets.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is only one published study that used a genetically informative design to investigate genetic influence on a pet-related measure. This study found that self-reports of frequency of playing with pets among a middle-aged, male twin sample had a heritability of h 2 = 0.29–0.37, indicating that genetic factors, which are likely mediated through individual differences in personality and related traits, play a role in establishing bonds with pets ( Jacobson et al, 2012 ). Surprisingly, the effects of shared environmental influences, which would include childhood exposure to pets, accounted for less than 10% of the variance in pet play during adulthood.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is also possible that there are genetically-influenced characteristics, such as human personality traits, which are shared between parents and children and may be related to attitudes and attachment to pets. A recent behavioral genetic study using adult male twin pairs reported that the heritability of frequency of play with pets in adulthood was as high as 0.37 and that residual effects of shared environmental factors (which would include childhood exposure to pets) were weak and not statistically significant (Jacobson, Hoffman, Vasilopoulos, Kremen, Panizzon, Grant, Lyons, Xian, & Franz, in press). Consequently, caution should be used when interpreting causality in future extensions of this research that may explore associations between attachment to dogs and individual differences in human socio-emotional well-being.…”
Section: Discussionmentioning
confidence: 99%